Research on Partial Reduction of Non-Essential Capabilities of Initiating Devices for Complex Mechanical Equipment Systems (Global Journals of Research in Engineering, 2023)
Currently modern spacecraft use high-precision equipment that is sensitive to shock impacts In this regard there is a need to create initiating devices with reduced impact This task determined the vector of development of electromechanical release devices that do not contain pyrotechnic means in their design Along with new challenges there are the constant problems of reducing weight increasing holding force and reducing response time The paper presents an analysis of the possibility of upgrading initiating devices in order to improve its characteristics A team of engineers conducts research using computational and experimental methods During the work samples of mechanisms were made and tested to confirm their performance
Keywords: initiating device; nichrome wire; torsion spring; reduction